EFFECTIVENESS OF STUDENT WORKSHEET BASED ON PROBLEM BASED LEARNING TO TRAIN CREATIVE THINKING ABILITY IN MATERIALS OF ENVIROMENTAL CHAGE - Elita Rahmawati; Sunu Kuntjoro (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Student worksheet is a teaching materials which used to help learning in the classroom and to increase student creativity. The student worksheet was designed using problem based learning to train creative thinking. Result of the interview with biology teacher in SMAN 18 Surabaya showed that the students' creative thinking skills are low, lesson plan didn’t show that trained creative thinking, the student worksheet was used by the teacher still contains cognitive questions, and didn’t train creative thinking. Creative thinking which was trained includes 4 aspects namely fluency, flexibility, originality, and elaboration. This research aimed to describe the effectiveness of student worksheet based on problem based learning to train creative thinking ability in materials of enviromental change. Enviromental change is material that presents authentic problem in life. The development students worksheet conducted with 4D models by define, design, develop without disseminate. The research was conducted in August 2018-March 2019 and student worksheet trials limited test for 20 students in class X SMAN 18 Surabaya. The data collection techniques used test method and response. The result of research were analyzed by quantitative. Student worksheet expressed very effective with the completeness of learning outcomes obtaining 90%. Student worksheet expressed very effective based students' responses obtaining 93,75%. Keyword : student worksheet, problem based learning, enviromental change, creative thinking.